HP-modified furnace tube market survey - Schillmoller, C. M. (Technical series (Nickel Development Institute (Canada)) ;, 1991)
This publication includes the market facts and projection for centrifugally cast high-alloy tube applications which were compiled in 1988 and 1989. Sources for the information included architect-engineering firms, furnace manufacturers, alloy producers, chemical, petrochemical and petroleum companies, and industrial publications.